128 Identification of Differentially Expressed Genes between High Placental Efficiency and Low Placental Efficiency Placentas on Day 95 of Gestation in Swine. (10th April 2018) - Krombeen, S K; Shankar, V; Noorai, R E; Saski, C A; Sharp, J L; Wilson, M E; Wilmoth, T A
Abstract: Placental efficiency (PE) describes the relationship between placental and fetal weights and is defined as fetal weight divided by placental weight. Within pig litters, PE can vary drastically, resulting in similarly sized pigs associated with very different placenta, up to a 50% weight difference. However, the means enabling the smaller placenta to grow a similarly sized littermate is unknown. The objective of this study was to determine the expression level of genes in the placental and associated endometrial tissue of high PE and low PE feto-placental units. Maternal line gilts ( n = 8) were ovario-hysterectomized on day 95 of gestation to obtain corresponding placental and endometrial samples from each feto-placental unit. PE was calculated to identify the most efficient and least efficient feto-placental unit in each litter; placental and endometrial samples from these units formed the high PE and low PE comparison groups. RNA sequencing was performed to identify differentially expressed genes (DEG) in high PE compared to low PE placental and endometrial tissues. Gene ontology enrichment analysis was also performed. In total, 214 DEG (false discovery rate P -value (FDR) < 0.10) were identified in the placenta and zero DEG (FDR < 0.10) were identified in the endometrium. Of the DEG in the placenta, 103 genes were upregulated (33 log fold change (logFC) ≥ 1; 70 0 < logFC < 1.0) and 111 genes were downregulated (49 logFC ≤ -1.0; 62 -1.0 < logFC < 0). The ten most upregulated genes have been implemented in immunomodulation, angiogenesis, fatty acid metabolism, gluconeogenesis, and ion homeostasis, while the ten most downregulated genes have been implemented in cell proliferation, transporter localization to the cell membrane, micronutrient transport, and metastasis. Beyond that, several transporters were upregulated including SLC45A3 a proton dependent sucrose transporter, ASIC1 a sodium ion transmembrane transporter, ATP13A3 a calcium ion transmembrane transporter, SLC4A7 a sodium bicarbonate cotransporter, SLC52A3 a riboflavin transporter, and SLC23A2 a sodium dependent ascorbate cotransporter. Additionally, LEP, CELA1, and CTSH encoding proteins with growth factor or angiogenic activity were upregulated. Conversely, genes ( KCNJ2, ABCC4, STEAP2 ) involved in ion (K +, Cl -, Cu 2+, Fe 3+ ) transmembrane transport were downregulated. Although a portion of the DEG identified in the pig placenta encode nutrient transporters and gene products with growth factor or angiogenic activity, DEG with alternative functions were also identified, indicating the complexity of the relationship between placental and fetal weights.